2006
DOI: 10.1177/107769900608300211
|View full text |Cite
|
Sign up to set email alerts
|

It's Gametime: The Maslach Burnout Inventory Measures Burnout of Sports Journalists

Abstract: A survey (N = 236) of newspaper sports journalists utilized the Maslach Burnout Inventory to examine burnout of sports editors, sports writers, and desk personnel (copy editors and page designers). Overall, sports journalists suffer moderate rates of emotional exhaustion and depersonalization and have a high rate of personal accomplishment, which can be interpreted as a degree of job satisfaction. Sports editors suffer from a higher rate of emotional exhaustion and depersonalization than sports writers or desk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 1 publication
3
22
0
Order By: Relevance
“…In the case of critical events, individual impact, the symptoms and traumatic experiences of PTSD and mental and emotional health obtain more than half of the answers, hence, partly corroborating previous data (e.g., Hatanaka et al, 2010; Morales et al, 2012; Weidmann et al, 2008) as far as the last two categories are concerned. Within the daily context, the most mentioned negative after-effects by the journalists interviewed were burnout, family context, mental and emotional health and physical health, in keeping with the findings of previous studies (e.g., Heloani, 2005; Reinardy, 2006). It should be noted that journalists mentioned burnout symptoms far more frequently when discussing their work on domestic news and PTSD symptoms when referring to working as special envoys.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the case of critical events, individual impact, the symptoms and traumatic experiences of PTSD and mental and emotional health obtain more than half of the answers, hence, partly corroborating previous data (e.g., Hatanaka et al, 2010; Morales et al, 2012; Weidmann et al, 2008) as far as the last two categories are concerned. Within the daily context, the most mentioned negative after-effects by the journalists interviewed were burnout, family context, mental and emotional health and physical health, in keeping with the findings of previous studies (e.g., Heloani, 2005; Reinardy, 2006). It should be noted that journalists mentioned burnout symptoms far more frequently when discussing their work on domestic news and PTSD symptoms when referring to working as special envoys.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to the daily work context, Strupp and Cosper (2001) state that the problem of journalists' occupational stress is not encountered in high adrenaline moments when covering a large-scale story, but rather in the daily routine of writing or reporting a day-to-day event. The main stress sources of journalists' daily work, identified in empirical studies, point to variables such as excessive working hours, deadlines, the work-family conflict, competition, low earnings, divergences with superiors, and lack of support from the organization (e.g., Heloani, 2005;Reinardy, 2006;Weidmann & Papsdorf, 2010). Hence, there is seemingly a predominance of organizational stressors in the daily work context of journalists.…”
Section: Occupational Stress: a Comprehensive Modelmentioning
confidence: 99%
“…The impact of the shutdown could alter the local sports broadcasting landscape. Scholars have already noted that burnout is a factor in the profession as local sports broadcasters are burdened with increasing responsibilities and demands with little help or compensation (Reinardy, 2006). Therefore, perhaps the main practical implication of this research is that it brings up the question that local sports broadcasters may not want to hear: Could news leadership determine that doing even more-with less-is possible?…”
Section: Discussionmentioning
confidence: 92%
“…Local sports broadcasters displayed their hard work, determination, and creativity throughout the pandemic; however, the strong performance might also suggest to management that fewer resources, higher expectations, less travel, and smaller departments may not impact viewership numbers. For sports broadcasters already facing tough job prospectsespecially for minorities and females (Hull & Romney, 2020;Sheffer & Schultz, 2007)-increasing burnout rates (Hull & Romney, 2020;Reinardy, 2006), and limited resources (Reinardy, 2012), suggesting they do more with less would likely exacerbate the exodus of experienced broadcasters. A study of the broadcast industry suggested that many reporters already see their jobs "as a three-to-fiveyear-type of profession.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual for journalists to accept and grow accustomed to a certain level of pressure and stress on the job. Deadlines, long work hours, and time away from loved ones are common place in this profession (Gloede, 1983;Kalter, 1999;Reinardy, 2006Reinardy, , 2008Reinardy, , 2009. And it is not uncommon for news workers to thrive under the demands, deadlines, and competition (Reinardy, 2012).…”
Section: Unstable Journalism Climate and Unfavourable Working Conditionsmentioning
confidence: 99%